New taxa of the genus Phyllostachys (Poaceae: Bambusoideae) from east China - Lai, Guang-Hui; Yue, Jin-Jun (Phytotaxa, 2022)
Phyllostachys viridivagina and P. hirtivagina var. glabrivagina, a species and a variety of Phyllostachys from east China, are described as new to science. Phyllostachys viridivagina is very particular in P. sect. Phyllostachys, and is easily distinguished from the other species of this section by young culms without pruina, greenish, sparsely brown spotted and abaxially glabrous culm leaf sheaths without pruina and with obvious veins, and apically shortly white ciliate culm leaf ligules. Phyllostachys hirtivagina var. glabrivagina is different from P. hirtivagina var. hirtivagina in having abaxially glabrous culm leaf sheaths and narrowly falcate culm leaf auricles.